Digital interfaces of historical newspapers: opportunities, restrictions and recommendations - Pfanzelter, Eva; Oberbichler, Sarah; Marjanen, Jani; Langlais, Pierre-Carl; Hechl, Stefan (Journal of data mining and digital humanities, 2021)
Many libraries offer free access to digitised historical newspapers via user interfaces. After an initial period of search and filter options as the only features, the availability of more advanced tools and the desire for more options among users has ushered in a period of interface development. However, this raises a number of open questions and challenges. For example, how can we provide interfaces for different user groups? What tools should be available on interfaces and how can we avoid too much complexity? What tools are helpful and how can we improve usability? This paper will not provide definite answers to these questions, but it gives an insight into the difficulties, challenges and risks of using interfaces to investigate historical newspapers. More importantly, it provides ideas and recommendations for the improvement of user interfaces and digital tools.